A dinâmica de (re)produção das queixas escolares e suas implicações nos modos de ser ético-moral segundo significações de crianças - Santos, Ruzia Chaouchar dos (2022)
This work aims to identify and analyze the dynamics of (re)production of school complaints engendered in the interpersonal relationships experienced by school-aged children and their instructions in ethical-moral ways of being, according to meanings produced by students of a municipal school located in Cuiabá-MT, in the context of the SARS-CoV-2 pandemic. In this process, twenty children were heard, among them a student identified with the complaint of indiscipline in the schooling experience and nineteen members of the class to which he was linked. The theoretical-methodological contribution adopted is anchored in the postulates of Historical-Cultural Psychology, wich are built on the foundations of historical-dialectical materialism. The procedures used for the data production were inspired by the ethnographic approach, favoring the participant observation of the dynamics of the educational routine in different configurations (synchronous, asynchronous and face-to-face), articulated with the realization of focus groups. The data were systematized in order to contribute to the collective efforts that has been mobilized to the process of denaturalizing the object status, which was historically conferred on this generational category in the scientific fiel, among other spheres of social life. For the process of analysis of the constructed information, the proposal of Meaning Nuclei was used. The analyzes reveal a strong adherence to the good/bad dichotomy, guiding the students' meanings about their peers identified with school complaints. Such meanings were circumscribed by teleological projects towards the come-to-be intertwined with the reproduction of objectivations of values of the dominant ethos, such as individualism, competition and concurrance, which are expressed in the focus of the student as the sole responsible for their scholar success or failure, fallaciously treated as merit or demerit. These principles, that are engendered in the ideological control of neoliberalism, tend to foster the phenomena of medicalization, pathologization and criminalization of childhood, embodied by determinations of social class, race and gender. At the same time, the existence, to a lesser extent, of elements that tend to empty the simplifying idea that permeates the dynamics of naturalization of the problems experienced by the “difficult child” in the schooling process was verified. In this regard, the participants indicated that the protected intersubjective relationships with their peers and with adults engendered by mediation of signs and sociocultural instruments that allow the appropriation of human-generic values, such as cooperation, alterity and solidarity, became incorporators in the (re)creation of alternatives and conscious choices towards collective confrontations with the eminently social school problem. This hinders the formation and development of ethical-moral ways of being guided by the appropriation of potentially emancipatory conquests that favor the promotion of humanization processes in their maximum possibilities of development